(untitled) (Communications in Computational Physics, 2008)
Flute mode turbulence plays an important role in numerous applications, such as tokamak, Z-pinch, space and astrophysical plasmas. In a low beta plasma flute oscillations are electrostatic and in the nonlinear stage they produce large scale density structures co-mingling with short scale oscillations. Large scale structures are responsible for the enhanced transport across the magnetic field and appearance of short scales leads to ion heating, associated with the ion viscosity. In the present paper nonlinear equations which describe the nonlinear evolution of the flute modes treated as compressible electromagnetic oscillations in a finite beta inhomogeneous plasma with nonuniform magnetic field are derived and solved numerically. For this purpose the 2D numerical code FLUTE was developed. Numerical results show that even in a finite beta plasma flute mode instability can develop along with formation of large scale structures co-existing with short scale perturbations in the nonlinear stage.